The athletic ability of college students Teacher preparation (Journal of the College of Basic Education, 2023)
The American National Board of Evaluation of Mathematics Achievement (NAEB) has placed increased emphasis on of athletic ability since the year (1990), when the evaluation operations that took place in the year (1966) focused and (2000) on inference, communication and problem-solving through building evaluation tasks that require Students link their learning across the mathematical fields, and the council believes that mathematical abilities (problem-solving - procedural knowledge - understanding of concepts (can be measured across mathematical content domains and it is important We make sure that measurements are taken of the student's ability to think in mathematical situations on the communication that he